Analysis of Government Policy on Education: Korelasi Tingkat Ekonomi Keluarga dengan Motivasi dan Prestasi Belajar Siswa - Yayuk Sri Wahyuni (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2017)
The study of this study attempts to reveal the achievement motivation, which is a genuine effort from a person to achieve a goal, whether he likes it or not likes to try to make it to be liked. With the motivation can also be an encouragement for students to play an active role in the learning process, so that students who have high motivation then can easily capture the material presented by the teacher, thus will affect the achievement in learning. Motivation is every activity undertaken by someone who is driven by a power from within a person, and a strong motivation to make someone able to work extra hard to achieve goals. Students who do not have the motivation to learn hard to do learning activities. This research is fruitful, that the study; the varying socioeconomic status of parents affects the students' learning motivation differently. This shows a significant influence between the socioeconomic status of parents and achievement motivation on student achievement.